Latin American expert opinion letter on the feasibility of systemic therapies in combination with locoregional therapies for hepatocellular carcinoma - Marìa Margarita Anders; Angelo Z. Mattos; José D. Debes; Oscar Beltran; Pablo Coste; Juan Ignacio Marín; Aline Lopes Chagas; Josemaría Menéndez; Enrique Carrera Estupiñan; Javier Diaz Ferrer; Angelo A. Mattos; Federico Piñero (Annals of Hepatology)
Recent advances in the systemic treatment of advanced hepatocellular carcinoma (HCC) with immunotherapy have once again reignited discussion over the role of combined therapy in earlier stages. This year, different international meetings have presented recent results from clinical trials on adjuvant therapy alone (IMBrave-050) and combined with transarterial chemoembolization (EMERALD-1 and LEAP-12). Increased enthusiasm for the use of adjuvant and neoadjuvant therapy for liver transplantation, surgery, and local-regional treatment of HCC has been shown. However, the initial results from these trials should be interpreted cautiously as we wait for final analyses and effects on overall survival. In this position paper from the special interest group from the Latin American Association for the Study of Liver Diseases (ALEH), we underline the caveats of the applicability of these potential treatments in our region, explore points of agreement, and highlight areas of uncertainty. Moreover, we underscore the role of hepatologists in the clinical decision-making process and management of these patients.